The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1017/s0007114508911533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea on kidney tubules of diabetic rats

Abstract: It has been documented that green tea (GT) and its catechin components improve renal failure and inhibit the growth of mesangial cells. In the present study we examined the long-term effect of GT extract on streptozotocin (STZ)-induced diabetic nephropathy and on the glycogen accumulation in the kidney tubules. Male Sprague -Dawley rats were randomly assigned to normal control groups (2, 6, 8 and 12 weeks) and five diabetic groups (n 10) of comparable age. A GT diabetic group received 16 % concentration of GT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
8
40
0
Order By: Relevance
“…These findings of present study are in agreement with the findings of Ramesh et al, Kim et al (2008) and Renno et al (2008) who showed tubular epithelial changes, enlargement of lining cells of tubules and accumulation of glycogen in the kidney tubules. Glycogen accumulation in the renal tubules could be attributed to hyperglycaemia induced by streptozotocin-induced diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…These findings of present study are in agreement with the findings of Ramesh et al, Kim et al (2008) and Renno et al (2008) who showed tubular epithelial changes, enlargement of lining cells of tubules and accumulation of glycogen in the kidney tubules. Glycogen accumulation in the renal tubules could be attributed to hyperglycaemia induced by streptozotocin-induced diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…The diabetic rats had increased levels of creatinine and urea which are considered as significant markers of renal function and this is in agreement with the present result. [37] Renno et al [38] demonstrated that green tea extract provides a beneficial effect on long-term diabetic nephropathy via suppressing hyperglycemia and preventing glycogen accumulation in the proximal tubules. The diabetic hyperglycemia induces elevation of the plasma levels of urea, uric acid and creatinine which are significant markers of renal dysfunction and reflecting a decline in the glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research using STZinduced rat as diabetic model revealed that the renal function, blood glucose and glycated protein profiles were improved in rats supplemented with green tea in the drinking water. Moreover, the renal mitochondrial reactive oxidative species (ROS) production of STZ-induced diabetic rat was also reduced by green tea (Renno, Abdeen, Alkhalaf, & Asfar, 2008). With regard to tannins, its scope of distribution in natural plant is diversified.…”
Section: Bioactive Components From Tcm Edible Plantsmentioning
confidence: 99%
“…Some kinds of (Renno et al, 2008) (continued on next page) mushrooms are used as functional foods as well as prescription ingredients in traditional medical system. Their hyperglycemic effects have been proven both experimentally and clinically (Perera & Li, 2011).…”
Section: Edible Plants Used As Functional Food For Diet Therapymentioning
confidence: 99%